2014
DOI: 10.1021/jf502919n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Distillation System and Yeast Strain on the Aroma Profile of Albariño (Vitis vinifera L.) Grape Pomace Spirits

Abstract: Orujo is a traditional alcoholic beverage produced in Galicia (northwest Spain) from distillation of grape pomace, a byproduct of the winemaking industry. In this study, the effect of the distillation system (copper charentais alembic versus packed column) and the yeast strain (native yeast L1 versus commercial yeast L2) on the chemical and sensory characteristics of orujo obtained from Albariño (Vitis vinifera L.) grape pomace has been analyzed. Principal component analysis, with two components explaining 74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Further, Matias-Guiu et al (34) state that methanol was the only head compound which maintained a similar concentration through the distillation. In contrast to our results, the results of Arrieta-Garay et al (44), there is no difference in methanol content (in grape pomace spirits) depending on the distillation system employed (alembic pot still or packed column distillations) while Léauté (8) and Garcia-Llobodanin et al (3) observed that the methanol content was higher in alembic distillates than column distillates.…”
Section: Fermentative Aroma Compounds Distillation Technique and Ageingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Further, Matias-Guiu et al (34) state that methanol was the only head compound which maintained a similar concentration through the distillation. In contrast to our results, the results of Arrieta-Garay et al (44), there is no difference in methanol content (in grape pomace spirits) depending on the distillation system employed (alembic pot still or packed column distillations) while Léauté (8) and Garcia-Llobodanin et al (3) observed that the methanol content was higher in alembic distillates than column distillates.…”
Section: Fermentative Aroma Compounds Distillation Technique and Ageingcontrasting
confidence: 99%
“…Although it has a limited sensory impact , its presence in spirits is important due to its toxicity. The concentration of methanol in all distillates in this study was <1200 g/hL of ethanol, which is the official limit of the European Council (N‐110/2008) for apple spirits. The concentration of methanol was influenced by both experimental factors and their interaction.…”
Section: Resultsmentioning
confidence: 78%
“…Despite the high content of this group of volatile components, no significant correlation was found between their total concentration and tasting assessment. Isobutanol and isoamylol, which are the main components of fusel oils, were contained in the studied samples in concentrations from 598 to 1100 mg/dm 3 a.a. and from 1300 to 2459 mg/dm 3 a.a, respectively, which significantly exceeded their threshold concentrations in aroma perception (Arrieta-Garay et al, 2014). However, it was found that the coefficients of pair correlation of these components with the organoleptic evaluation of distillates had low values (0.115 and 0.087), respectively.…”
Section: Resultsmentioning
confidence: 86%
“…However, most of the current investigations on CCA have been devoted to the analysis and bioactive effects of the non-volatile substances [ 10 , 11 ] and the investigations on volatile components of CCA have been rarely reported. A series of methods can be used to obtain the volatile flavour compounds of CCA like distillation [ 12 ], Headspace-solid phase microextraction (HS-SPME) [ 13 ], solid-phase extract (SPE) [ 14 ], simultaneous distillation and extraction (SDE) [ 15 , 16 ] and so on. Mao et al [ 17 ] studied the volatile components of CCA from Shangdong by gas chromatography–mass spectrometry (GC–MS) analysis of distilled samples.…”
Section: Introductionmentioning
confidence: 99%